Profil Hasil Belajar Peserta Didik Kelas X MIPA SMA pada Materi Virus menggunakan Model Flipped Classroom - Chaer, Muhammad Ainun; Nurhayati B, Nurhayati B; Palennari, Muhiddin (Universitas Negeri Makassar, 2021)
Abstract. This study aims to determine student learning outcomes and the effectiveness of the Flipped Classroom learning model using E-Learning on the learning outcomes of class X MIPA students at Madrasah Aliyah Negeri 2 Bone. This research is a pre-experimental research design using One Group Pretest-Postest. The population in this study were students of class X Madrasah Aliyah Negeri 2 Bone. The research sample was selected with a specific purpose (purposive sampling), namely the technique of determining the sample with certain considerations in order to obtain one class, namely class X MIPA 1, totaling 27 students. The data collection technique used is through tests. The collected data were analyzed using descriptive statistics and inferential statistics. The results showed that the posttest mean score of 74.07 was higher than the posttest average score of 28.74. Based on the results of the data analysis obtained, it can be concluded that the learning outcomes of students who are taught with the flipped classroom model have an average value that is in the good category and the Flipped Classroom learning model is effective on student learning outcomes on virus material for Class X MIPA 1 Madrasah Aliyah Negeri 2 Bone.Keywords: learning models, Flipped Classroom, learning outcome